Phylogeny of the Ichthyopterygia incorporating recent discoveries from South China. Issue 1 (2nd January 2016) - Ji, Cheng; Jiang, Da-Yong; Motani, Ryosuke; Rieppel, Olivier; Hao, Wei-Cheng; Sun, Zuo-Yu
ABSTRACT: During the last decade, abundant ichthyopterygian material has been found from the Triassic of South China as well as the Upper Jurassic and Lower Cretaceous of Europe and South America, significantly expanding our knowledge of ichthyopterygian diversity through the Mesozoic. Previous phylogenetic hypotheses of the group no longer account for these extensive additions, necessitating a new phylogenetic framework for the entire Ichthyopterygia to enable evolutionary studies of the group. We present here a comprehensive phylogenetic hypothesis for Ichthyopterygia based on cladistic analysis of 163 characters coded for 59 ingroup and five outgroup taxa. The monophyly of Ichthyopterygia is strongly supported by a Bremer index value of 7. Five major groups of Ichthyopterygia during the Triassic, viz., Grippioidea, Cymbospondylidae, Mixosauridae, Shastasauridae, and Toretocnemidae, are well supported by Bremer index values between 3 and 5. Major clades that evolved in the Triassic, including Merriamosauria, Euichthyosauria, and Parvipelvia, are also robustly supported, whereas most post-Triassic clades are very weakly supported with a Bremer index value of 1, with a few exceptions, such as Thunnosauria and Ophthalmosauridae. The traditional Shastasauridae is expanded to comprise six genera but excludes Callawayia, which is more closely related to Parvipelvia than to Shastasauridae. ' C. ' wolonggangensis is a shastasaurid but does not form a monophyletic clade with Callawayia neoscapularis or Guizhouichthyosaurus tangae as previously asserted. The new phylogenetic hypothesis is generally consistent with the stratigraphic occurrences of each taxon especially for the Triassic taxa. http://zoobank.org/urn:lsid:zoobank.org:pub:901B6FB6-2D80-4AE9-B017-A0226175AFDA SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Ji, C., D.-Y. Jiang, R. Motani, O. Rieppel, W.-C. Hao, and Z.-Y. Sun. 2015. Phylogeny of the Ichthyopterygia incorporating the recent discoveries from South China. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2015.1025956.